Triheptanoin: A Rescue Therapy for Cardiogenic Shock in Carnitine-acylcarnitine Translocase Deficiency - Mahapatra, Sidharth (JIMD Rep, 2017)
Carnitine-acylcarnitine translocase (CACT) deficiency is a rare long-chain fatty acid oxidation disorder (LC-FAOD) with high mortality due to cardiomyopathy or lethal arrhythmia. Triheptanoin (UX007), an investigational drug composed of synthetic medium odd-chain triglycerides, is a novel therapy in development for LC-FAOD patients. However, cases of its safe and efficacious use to reverse severe heart failure in CACT deficiency are limited. Here, we present a detailed report of an infant with CACT deficiency admitted in metabolic crisis that progressed into severe cardiogenic shock who was successfully treated by triheptanoin. The child was managed, thereafter, on triheptanoin until her death at 3 years of age from a cardiopulmonary arrest in the setting of acute respiratory illness superimposed on chronic hypercarbic respiratory failure.